Determinan Minat Menabung di Bank Syariah pada Pegawai Yayasan Sunan Kalijogo Jabung - Mulyani, Sri (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2023)
Knowledge and brand image are two of the aspects that affect Sunan Kalijogo Jabung Foundation employees' enthusiasm in saving money. The goal of this study is to ascertain, partially simultaneously, the impact that Knowledge, Trust, and Brand Image have on Sunan Kalijogo Jabung Foundation employees' desire to save money. Quantitative approaches are employed in this study. There were 272 responders in total, all of whom worked for the Sunan Kalijogo Jabung Foundation. With 74 responses, the sample size was obtained using simple random sampling as the method. Multiple linear regression is the data analysis method used in this study, which makes use of the SPSS 17 For Windows program. The estimated t result of the influence of knowledge on interest in saving money is 4,006 greater than the t table, or 0.677 (4,006 > 0.677), with a significance level of 0.00, according to the t test. This indicates that employees' desire in saving money in Islamic banks is positively and significantly impacted by the knowledge variable. Next, with regard to the Brand Image variable, the t-test reveals that, with a significance of 0.00, the t-calculated result of the effect of Brand Image on interest in saving money is 3,837 greater than the t table, or 0.677 (3,837 > 0.677). This indicates that employees' desire to save money at Islamic banks is positively and significantly impacted by the Brand Image variable. Based on the f test results, the value is 69.153, more than 3.09 (69.153>3.97) with a significance level of 0.00 in the f table. Thus, it can be said that it significantly influences people's desire to save money in Sharia Banks in Malang Regency at the same time.